The private sector in the development landscape: partnerships, power, and questionable possibilities. Issue 7 (3rd October 2021) - Hart, Jason; Russon, Jo-Anna; Sklair, Jessica
ABSTRACT: In introducing the Special Issue on The Private Sector in the Development Landscape this article focuses upon three key themes all related, in some manner, to the issue of power. These themes are drawn from the critique of partnership amongst conventional development actors and provide a framework for discussion of the six full-length articles and three shorter practice pieces that follow. The first theme for discussion is finance and the impact of its distribution within partnerships involving private and public / third sector actors. We then consider such partnerships in historical context, paying attention to the legacy of colonialism and global North-South dynamics. Finally, we explore the potential for power relations to be renegotiated within partnerships. Considering insights offered by the assembled authors and our own reading of the literature we suggest that partnership involving the private sector appears to do little in shifting development dynamics in a more egalitarian direction. Indeed, it may entrench underlying inequity. We conclude by questioning the extent to which the challenges of partnership with the private sector can be overcome without parallel efforts to bring greater accountability, transparency, and equity to the private sector's own activities, regardless of its engagement in development.